Caracterização da chuva simulada em tunel de vento por diferentes metodos - Colares, Matheus de Figueiredo Braga (2016)
Soil loss by water erosion can be estimated by empirical equations that depend on the kinetic energy of the rain. Determining this energy is of great importance, given that it characterizes rain erosivity. One of the largest research centers in erosion is the International Center of Eremology – I.C.E., located in Ghent, Belgium, which objective is to study the formation of deserts. It was used to evaluate the characteristics of simulated rain, measuring the speed and kinetic energy of rain simulated within the tunnel by means of two disdrometers: the UFLA-DRGS and the OTT Parsivel2 (OTT LASER equipment). The testing conditions allowed us to verify the effect of operating pressure of the rain simulator nozzles, the evaluation height (proximity to the spray), the presence or absence of wind, and the position of the equipment in relation to the nozzles. After 216 trials, we verified that the disdrometers were similar to each other regarding the capacity for evaluating drop speed. In addition, there was clear influence of the wind, altering the trajectory of the drops in more than 45 degrees, and increasing drop speed and kinetic energy of the rain. We also verified that the rain differs according to the evaluated position, that is, under spray or between sprays.